Knowledge and practice of opioid-free anaesthesia for non-bariatric surgery in an academic hospital: A cross-sectional study. - Gonyora, Simbarashe; Mamoojee, Anisah Ismail (Student’s Journal of Health Research Africa, 2026)
Background: The liberal use of opioids peri-operatively is a matter of concern in contemporary medical practice and carries the risk of numerous potentially undesirable effects. Multimodal Opioid-Free Anaesthesia (OFA) has been proven to reduce the incidence of the potentially undesirable effects of opioids beyond the initial premise of bariatric surgery. Methods: This descriptive, contextual, cross-sectional study was conducted from February 2022 through to February 2023. The study population was limited to 224 anaesthesia providers working in academic hospitals affiliated to the University of the Witwatersrand (Wits) Department of Anaesthesiology. The data for this study were collected by distributing an online questionnaire, which was formulated based on the available literature to ensure content validity. Data extracted included: years of anaesthetic experience, professional rank, affiliated Hospital, special training in OFA, and the answers to various aspects of knowledge and practice of OFA. Results: 143 anaesthesia providers participated in the study. A statistically significant difference in OFA knowledge level was observed among the hospitals, as determined by the Kruskal-Wallis test (H = 13.9, p = 0.046). Chris Hani Baragwanath Academic Hospital (CHBAH) and Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) had the highest percentage of respondents with knowledge of OFA, 38.5% and 25.9%, respectively. A significant number of participants reported not having any knowledge of OFA protocols (p = 0.030); additionally, more participants indicated that their hospital did not have a formal OFA protocol (p < 0.001). Conclusion: The study revealed a lack of knowledge of OFA for non-bariatric surgery and multiple challenges anaesthesia providers are confronted with in the adoption of OFA in clinical practice. Recommendations: Training programmes that mandate involvement in research activities, journal clubs, and CPD events focused on OFA. Hospital-specific OFA protocols based on resources available would encourage the practice of OFA.